From the Ancient near East to Christian Byzantium: Kings, Symbols, and Cities - Baghos, Mario (Cambridge Scholars Publisher, 2021)
This book combines concepts from the history of religions with Byzantine studies in its assessments of kings, symbols, and cities in a diachronic and cross-cultural analysis. The work attests, firstly, that the symbolic art and architecture of ancient cities--commissioned by their monarchs expressing their relationship with their gods--show us that religiosity was inherent to such enterprises. It also demonstrates that what transpired from the first cities in history to Byzantine Christendom is the gradual replacement of the pagan ruler cult--which was inherent to city-building in antiquity--with the ruler becoming subordinate to Christ; exemplified by representations of the latter as the 'Master of All' (Pantokrator). Beginning in Mesopotamia, the book continues with an analysis of city-building by rulers in Egypt, Greece, and Rome, before addressing Judaism (specifically, the city of Jerusalem) and Christianity as shifting the emphasis away from pagan-gods and rulers to monotheistic perceptions of God as elevated above worldly kings. It concludes with an assessment of Christian Rome and Constantinople as typifying the evolution from the ancient and classical world to Christendom.